Organizational learning, innovation and performance: a study of Malaysian small and medium sized enterprises. - Mohamed Salim, Islam; Sulaiman, Mohamed (Canadian Center of Science and Education, 2011)
This empirical study attempts to investigate the effect of organizational learning on innovation as well as the impact of innovation on company performance. Based on the literature review, two hypotheses are proposed to guide the study: the positive impact of organizational learning on innovation and the positive relationship between innovation and performance. Data was collected via electronic survey from 320 small and medium enterprises operating in the ICT industry in Malaysia. Findings from the study support both the two hypotheses thus providing further evidence that organizational learning contributes to innovation capability, and that innovation is positively related to firm performance. Several guidelines and practical implications from the study are also discussed.